운동처방을 적용한 숲길 걷기가 노인의 신체조성에 미치는 영향 - 김초윤; Choyun Kim; 이윤정; Yunjeong Yi; 박범진; Bum-jin Park; 송초롱; Chorong Song (한국산림과학회지, 2024)
본 연구는 운동처방을 적용한 숲길 걷기 운동이 노인의 신체조성에 미치는 영향을 밝히는 것을 목적으로 수행되었다. 연구대상자는 65세 이상 75세 미만의 노인 44명(평균연령: 69.3±3.1세)으로 하였다. 실험군 22명은 개인의 건강상태 등을 고려하여 처방된 운동강도를 바탕으로 매주 3회, 회당 1시간 이상의 숲길 걷기를 8주 동안 진행하였다. 대조군 22명은 평소와 같은 생활을 지속하였다. 실험군 및 대조군의 8주 동안의 체성분 변화를 측정하였으며, ①실험군의 숲길 걷기 전후 비교, ②대조군의 사전 사후 측정 결과 비교, ③실험군과 대조군의 변화량(사후-사전) 비교의 3가지 관점에서 분석을 진행하였다. 그 결과, ①실험군에서 체중, 체지방, 체질량 지수에서의 유의한 감소, ②대조군에서 오른팔 근육량 및 비율, 몸통 근육 비율, 왼쪽 다리의 근육량 및 비율, 오른팔 체수분의 유의한 감소가 나타났으며, ③그룹 간 비교결과, 실험군은 체중 및 체지방이 감소한 반면 대조군은 증가하였다는 사실을 알 수 있었다. 결론적으로, 운동처방을 적용한 숲길 걷기는 노인의 신체조성에 긍정적인 영향을 미친다는 것이 밝혀졌다. This study aimed to investigate the effects of forest walking based on an exercise prescription on body composition of older adults. Forty-four older adults (average age: 69.3 ± 3.1 years) participated in this study. The experimental group engaged in forest walking based on a prescribed exercise intensity considering the participants' respective health conditions. The participants walked three times a week for more than an hour each time for 8 weeks. By contrast, the participants in the control group spent their days according to their usual lifestyle. The analysis involved the following: ① a comparison of the measurements taken before and after the 8-week period of forest walking in the experimental group, ② a comparison between pre- and post-study measurements in the control group, and ③ a comparison of the changes (post-study minus pre-study values) between the experimental and control groups. The results were as follows: ① the experimental group showed significant decreases in weight, body fat mass, and body mass index; ② the control group exhibited significant decreases in muscle mass and ratio in right arm and left leg, muscle ratio in trunk, and body water mass in right arm; and ③ weight and body fat index decreased in the experimental group but increased in the control group. In conclusion, forest walking based on an exercise prescription had a positive impact on body composition of older adults.